Anatomical Justification of Extradural Resection of the Anterior Clinoid Process - Sufianov, Albert A.; Iakimov, Iurii A.; Garifullina, Nargiza A.; Sufianov, Rinat A.; Kovalenko, Roman V.; Kosimzoda, Idrisdzhoni A. (Asian Journal of Neurosurgery, 2023)
Objective The study aimed to provide neuroanatomical justification of the extradural resection of the anterior clinoid process (ACP).Material and Method Using a cross-sectional study design, 47 cranial computed tomography (CT) scans were examined. There were 31 (65.96%) females aged 28 to 79 years. The measured dimensions were ACP length and width, and optic strut (OS) width. Index (iacp) was measured as the ratio of ACP width to ACP length. The ACP volume and working operating field (WOF) volume were measured using Syngo.via Siemens program. The percentage expansion of WOF after removal of the ACP was estimated on 5 fixed human cadaver heads with the exoscope VITOM 3D. The possibilities of the combined approach were demonstrated in a clinical case.Results The mean ACP lengths were 11.31 ± 2.76 and 11.54 ± 2.86 mm, on the right and left, respectively. The mean ACP widths were 7.70 ± 1.66 and 7.64 ± 1.67 mm, on the right and left, respectively. Average iacp was 0.67 (minimum 0.45; maximum 0.90). The width of the OS varied in the range from 1.37 to 4.75 mm. The average volume of right ACP was 0.71 ± 0.16 cm3, right WOF was 3.26 ± 0.74 cm3, left ACP was 0.71 ± 0.15 cm3, left and WOF was 3.20 ± 0.76 cm3. Removal of the right ACP expanded the right WOF by 22.21 ± 3.88%, and left ACP by 22.78 ± 5.50%. There was an approximately 25% increase in the WOF from the cadaveric dissections. Taking into account the variability of the ACP and OS, we proposed our own surgical classification of complicated (iacp ≥ 0.67; medium OS 2.5 mm ≤ 4.0 mm; wide OS ≥ 4.0 mm; ACP with pneumatization) and uncomplicated ACP (iacp 0.45 ≤ 0.67 mm; iacp ≤ 0.45; narrow OS ≤ 2.5 mm; ACP without pneumatization). Using this classification, we developed an algorithm for ACP dissection and removal. This was piloted in a clinical case of microsurgical clipping of a left internal carotid artery-posterior communicating artery aneurysm via the left minipterional approach.Conclusion Extradural removal of ACP expands the WOF by approximately 25%, it helps neurosurgeons to improve proximal vascular control and avoid complications, and expands the range of indications for neurosurgical interventions in the skull base area.
Keywords: anterior clinoid process; optic strut; clinoidectomy; keyhole approach; aneurysm